Interspecies variation in orbital bone structure of psittaciform birds (with emphasis on Psittacidae) - Machado, M.; Schmidt, EMD; Montiani-Ferreira, F. (Blackwell Publishing, 2006)
Objectives: This text presents an anatomical study of the normal bony orbital structure of a sample of different bird species belonging to the order Psittaciformes.Procedures: the bony anatomy of Psittaciformes' skulls was examined and described using cadavers of birds that were presented already dead to the Federal University of Parana, Brazil or had been euthanized for humane reasons. Dissections of the orbital cavity were performed under 2-4 x magnification, and descriptions of the orbital bones were made from observations of macerated skulls that had been boiled and cleaned. The present paper discusses the main features of the bony orbit of psittaciform birds, describing known anatomical information but also bringing new information, mainly concerning species differences that might help not only veterinary anatomists but also zoologists, clinicians, researchers, and students of veterinary ophthalmology to better comprehend this order of birds.Results and conclusions: Variations in the anatomic conformation of the bony elements of the orbit were observed in different species of Psittaciformes. Based on these differences, Psittaciformes were classified into two different groups. The first group of Psittaciformes shows an enclosed (complete) bony orbit formed by the junction of the orbital with the postorbital processes, creating a suborbital arch. The second group of Psittaciformes essentially lacked a suborbital arch, presenting an open (incomplete) bony orbit, typical of most modern birds. In the latter group, orbital and postorbital processes are present.
Keywords: anatomy; cladistics; enclosed (complete) orbit; open (incomplete) orbit; Psittaciformes